O corpo, esse desconhecido - Doin, Rafael Romeiro (Universidade Federal de São Carlos, 2017)
The main problem of the present study is to investigate: how is body self-image built in school? To answer this question, I looked at myself in a process of video recording and, following on, developed a research project and this work, which is configured in a bibliographical research and autobiographical character. The autobiographical method was constituted as a formative dimension and, together with the bibliographical survey and the literature analysis, led to the following axes of reflection: brief history of the body; cultural aspects and consumption; body language and the perception of a speaking body; the corporeality in the experience of the teacher.
The body, that unknown
Keywords: Autoimagem corporal; Body self-image; Corpo e educação; Body and education; Formação de professores; Teacher education; Identidade eu-corpo; I-body identity; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO